2014
DOI: 10.1117/1.oe.53.2.023101
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric linear array sensor for object recognition

Abstract: Abstract. This paper presents a proof of concept sensor system based on a linear array of pyroelectric detectors for recognition of moving objects. The utility of this prototype sensor is demonstrated by its use in trail monitoring and perimeter protection applications for classifying humans against animals with object motion transverse to the field of view of the sensor array. Data acquisition using the system was performed under varied terrains and using a wide variety of animals and humans. With the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Large numbers of research results have indicated that it is feasible to determine which objects are human and which are animal based on these differences, but the current research is generally concerned with the acquisition and recognition of the object profile image [3][4][5][6][7][8]. For image acquisition, the most common method is the use of a linear array sensor to acquire the moving object image [9][10][11], but the acquired image is relatively simple and cannot show the object in greater detail, meaning that it is difficult to distinguish between similar actions on different objects. Therefore, how to obtain higher-resolution images when using only a small number of sensors has become a question that is worthy of exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of research results have indicated that it is feasible to determine which objects are human and which are animal based on these differences, but the current research is generally concerned with the acquisition and recognition of the object profile image [3][4][5][6][7][8]. For image acquisition, the most common method is the use of a linear array sensor to acquire the moving object image [9][10][11], but the acquired image is relatively simple and cannot show the object in greater detail, meaning that it is difficult to distinguish between similar actions on different objects. Therefore, how to obtain higher-resolution images when using only a small number of sensors has become a question that is worthy of exploration.…”
Section: Introductionmentioning
confidence: 99%